2018
DOI: 10.1007/s11682-018-9939-4
|View full text |Cite
|
Sign up to set email alerts
|

Smaller subcortical volume in Parkinson patients with rapid eye movement sleep behavior disorder

Abstract: Parkinson disease (PD) patients with rapid eye movement (REM) sleep behavior disorder (RBD) have worse motor symptoms and non-motor symptoms than patients without RBD. The aim of this study was to examine underlying differences in brain structure from a network perspective. Baseline data were obtained from Parkinson's Progression Markers Initiative (PPMI) participants. We divided PD patients and healthy controls (HC) into RBD positive and RBD negative using a cutoff score of ≥5 on the RBD screening questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…It also regulates sleep and wakefulness. Some previous morphometry studies showed markedly reduced gray matter volume in the bilateral thalamus of PD-pRBD patients in comparison with PD-npRBD patients and the volume of thalamus is negatively correlated with RBDSQ scores (7,8,12). And some previous functional studies also reported changes of thalamus function.…”
Section: Increased Efficiency Of Bilateral Thalamus (Pd-prbd Vs Pd-nmentioning
confidence: 89%
See 2 more Smart Citations
“…It also regulates sleep and wakefulness. Some previous morphometry studies showed markedly reduced gray matter volume in the bilateral thalamus of PD-pRBD patients in comparison with PD-npRBD patients and the volume of thalamus is negatively correlated with RBDSQ scores (7,8,12). And some previous functional studies also reported changes of thalamus function.…”
Section: Increased Efficiency Of Bilateral Thalamus (Pd-prbd Vs Pd-nmentioning
confidence: 89%
“…Based on these results, we speculate that the increased betweenness centrality of the left insula is compensatory to volume decrease and pathological involvement to maintain the overall information conversion efficiency of the brain. However, some studies based on morphometry did not find any significant difference in limbic system (7,12,14). The difference may be due to the size of the sample and the severity of the patient's symptoms.…”
Section: Increased Efficiency Of Bilateral Thalamus (Pd-prbd Vs Pd-nmentioning
confidence: 93%
See 1 more Smart Citation
“…In PD patients with polysomnography-confirmed rapid eye movement sleep behavior disorder (RBD), cortical thinning was reported in the right perisylvian and inferior temporal cortices together with shape changes in the putamen compared to PD without RBD ( 42 ). Likewise, decreased volume in the right putamen correlating with RBD symptom severity was identified in PD with RBD vs. those without ( 43 ). On susceptibility-weighted imaging, loss of dorsal nigral hyperintensity (corresponding to nigrosome-1) was observed in ~25% of patients with idiopathic RBD, which associated with lower putaminal dopamine transporter (DAT) binding on single-photon emission computed tomography (SPECT) ( 44 ).…”
Section: Structural Neuroimaging In Parkinsonian Disordersmentioning
confidence: 92%
“…Some studies have found that these patients had reduced gray volume in the thalamus, putamen, lingual gyrus, cerebellum, pontomesencephalic tegmentum, amygdala, anterior cingulate gyrus, posterior cingulate gyrus, and hippocampus [ 12 16 ]. However, some methodological limitations are still shown in these studies, especially the lack of diagnosis of RBD by polysomnography (PSG) [ 13 , 15 ]. Studies have indicated changes in functional connectivity (FC) in idiopathic RBD [ 17 , 18 ], but research on FC in PD-RBD is scarce, and no study to date has explored the structural and functional differences between PD-RBD and PD without RBD (PD-nRBD) in combination with VBM and FC.…”
Section: Introductionmentioning
confidence: 99%